Textile-Based Weft Knitted Strain Sensors: Effect of Fabric Parameters on Sensor Properties - Atalay, Ozgur; Kennon, William; Husain, Muhammad (Sensors (Basel, Switzerland), 2013)
The design and development of textile-based strain sensors has been a focus of research and many investigators have studied this subject. This paper presents a new textile-based strain sensor design and shows the effect of base fabric parameters on its sensing properties. Sensing fabric could be used to measure articulations of the human body in the real environment. The strain sensing fabric was produced by using electronic flat-bed knitting technology; the base fabric was produced with elastomeric yarns in an interlock arrangement and a conductive yarn was embedded in this substrate to create a series of single loop structures. Experimental results show that there is a strong relationship between base fabric parameters and sensor properties.